"Fifty Questions": Encouraging Students to Ask Questions and Evaluate Information. Issue 1 (20th December 2016) - Bhavsar, Victoria Mundy; Dypiangco, Cristina M.; Moreau, Rob
Abstract : Core Ideas: Students need support in learning to productively question received information. Students make clear progress in the ability to find and evaluate information. Students do not clearly progress in the ability to formulate sophisticated questions. Two common learning goals in general education science classes are (1) students are able to formulate carefully considered, evidence‐based conclusions and (2) students are able to locate and critically evaluate relevant information. To support students in these outcomes, "50 Questions" was created. This multi‐step assignment required students to generate many questions, refine one question to investigate, and to gather and evaluate relevant information. The assignment was used in several terms of "AG 101: Agriculture in the Modern World." This article provides the assignment and gives suggestions for improving the assignment for instructors who wish to adopt it. Based on quantitative and qualitative analysis, student work products clearly demonstrated that students made progress from their freshman/sophomore years to their junior/senior years in locating high quality information and being able to evaluate its quality correctly. However, student work did not clearly demonstrate that students made progress in formulating sophisticated questions as they advanced as undergraduates; extra instruction may be needed to support students in this important aspect of formulating inquiries that can lead to robust conclusions. With this caveat in mind, we conclude that the 50 Questions assignment provided an effective entry into the first steps of the critical reading and writing process, supporting student learning while easing the grading burden.